PROSPEK USAHA MEUBEL KAYU DI KECAMATAN ARGA MAKMUR - Mardiati Sari, Dian (JURNAL EKOMBIS REVIEW, 2016)
The aim in this study was to determine and analyze the wooden furniture business prospects in Sub Arga Makmur. This research using descriptive analysis. Results of this research is the length of a business carried on in the wooden furniture business unit Arga Makmur District of average between 1015 years, namely by 60%. The average amount of labor which is owned by each business unit wooden furniture in Arga Makmur District of average between 1-3 labor as many as 19 business units or about 63.3%. The amount of capital spent by the wooden furniture business in Arga Makmur District of Rp 10,000,000, - with a business turnover of wood furniture production bekisar Rp 10,000,000, - s/d Rp 15.000.000, - per month. The entrepreneurs receive income ranges between Rp 2.000.000, - s/d Rp 3,000,000, - per month. In addition, the wooden furniture business in District Arga Makmur is also able to open the field of business and labor intensive. Constraints faced by businesses wood furniture is a lack of education employers and labor, the lack of market infrastructure, lack of technology used. Pengelolahan wood furniture businesses in the district Arga Makmur still simple. However, the wooden furniture business in Sub Arga Makmur able to provide considerable benefits to employers and can increase local economic development. Business opportunities will be made better if the constraints faced in running a business is able to overcome with good.  Key Words: Business Prospect, Employment, Capital